2022
DOI: 10.3389/ti.2022.10185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pretransplant Renal Replacement Therapy on Clinical Outcome After Isolated Heart Transplantation

Abstract: End stage renal disease (ESRD) is a contraindication to isolated heart transplantation (HT). However, heart candidates with cardiogenic shock may experience acute kidney injury and require renal replacement therapy (RRT) and isolated HT as a life-saving operation. The outcomes, including survival and renal function, are rarely reported. We enrolled 569 patients undergoing isolated HT from 1989 to 2018. Among them, 66 patients required RRT before HT (34 transient and 32 persistent). The survival was worse in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Infection remained the leading cause of mortality in both groups in this study. Our previous research found that post-transplant dialysis and early bloodstream infection contributes to a 5.5-fold and 3.43-fold increase in early mortality, respectively [ 18 , 21 ]. In the present study, the PCCS group exhibited a higher incidence of certain factors, namely, post-transplant ECMO support (29%), delayed sternum closure (31%), early bloodstream infection (18%), and dialysis (41%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection remained the leading cause of mortality in both groups in this study. Our previous research found that post-transplant dialysis and early bloodstream infection contributes to a 5.5-fold and 3.43-fold increase in early mortality, respectively [ 18 , 21 ]. In the present study, the PCCS group exhibited a higher incidence of certain factors, namely, post-transplant ECMO support (29%), delayed sternum closure (31%), early bloodstream infection (18%), and dialysis (41%).…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, sternal closure may be delayed for 24 h if adequate hemostasis is not achieved. Furthermore, immunosuppressant and desensitization protocols were followed as usual, based on previous publications [18][19][20][21].…”
Section: Management Of Patients With Pccs Receiving Htmentioning
confidence: 99%